Climates and weather explained : an introduction from a southern perspective - Linacre, Edward, 1925- (Routledge, 1997)
This comprehensive introduction, complete with free, networkable CD-ROM, integrates climatology and meteorlogy to study the atmosphere. Includes many illustrations and case studies and additional interactive material on the CD-ROM.